2019
DOI: 10.17116/jnevro201911908168
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of blood flow indicators in pathological kinked internal carotid arteries with their orthostatic and rotational positions

Abstract: Резюме Цель исследования. Оценка динамики характера кровотока у пациентов с гемодинамически значимыми патологическими извитостями (ПИ) внутренних сонных артерий (ВСА) при их ортостатической и ротационной транспозициях. Материал и методы. Обследованы 86 пациентов (35 с ПИ ВСА на фоне дисплазии соединительной ткани и 51 с ПИ ВСА вследствие гипертонической болезни) и 20 условно здоровых людей. Всем больным было проведено дуплексное сканирование. Все показатели оценивали в положении пациента лежа на спине и при фу… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Utilizing Doppler ultrasound, it was found that hemodynamic parameters in PK ICA due to FMD showed a decrease in blood flow velocity when patients were standing, suggesting more pronounced hemodynamic impairment in hypertensive heart disease. S-shaped kinks significantly increased blood flow turbulence, indicating that the position of ICA kinking is critical for detecting changes in blood flow dynamics [ 22 ]. Another study identifies tortuosities and coiling of the ICA as factors associated with pulsatile tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing Doppler ultrasound, it was found that hemodynamic parameters in PK ICA due to FMD showed a decrease in blood flow velocity when patients were standing, suggesting more pronounced hemodynamic impairment in hypertensive heart disease. S-shaped kinks significantly increased blood flow turbulence, indicating that the position of ICA kinking is critical for detecting changes in blood flow dynamics [ 22 ]. Another study identifies tortuosities and coiling of the ICA as factors associated with pulsatile tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prevalence of DICA in the general population, according to few and conflicting statistical data, varies within a fairly wide range, from 10 to 40%. 3,4 For example, the latest calculations presented by Balevi indicate that bilateral DICA occurs in 30.5% of cases. 5 In another study by Di Pino et al, the prevalence of carotid artery anomalies among adults and children did not exceed 9.9%.…”
mentioning
confidence: 99%